Definição de framework para a padronização de processos em um periódico científico com base em revisão da literatura e nos objetivos de desempenho - Garcia, José Augusto Campos [UNESP]; Oliveira, Marina Buranelli de [UNESP]; Rodrigues, José de Souza [UNESP]; Albino, João Pedro [UNESP] (A Fundacao para o Desenvolvimento de Bauru (FunDeB), 2014)
This work presents the results of a study that aimed to establish a framework to standardize the process of a scientific journal. It has a team that performs operational routines regulated by standards (external) and patterns (internal and external). The high turnover rate of the supportive team has generated information loss and increased service variability. The research started from the assumption that the process standardization (which includes the formalization) could be a way to reduce this secondary effect. Standardization techniques were identified through a literature review of the main national and international databases of journals and congresses. The identified standardization techniques were analyzed considering the number of times they appeared in the papers analyzed and performance objectives proposed by Slack et al. (2009). As result of this research, a framework was obtained for the standardization of processes adapted to the needs of the journal studied. The model is feasible to be used more widely, given its structural similarity to the one proposed by Campos (2004), a Brazilian model that is a reference in the field.

Este trabalho apresenta o resultado de uma pesquisa cujo objetivo foi estabelecer um framework para padronização de processos em um periódico científico. Ele tem uma equipe que executa rotinas operacionais reguladas por normas (externas) e padrões (internos e externos). A rotatividade elevada de membros da equipe de apoio (bolsistas) gerava perda de informação e aumentava a variabilidade da qualidade do serviço prestado. A pesquisa partiu do pressuposto de que a padronização (que inclui a formalização) dos processos poderia ser uma forma de reduzir este efeito secundário. Técnicas para padronização foram identificadas a partir de revisão da literatura nas principais bases de dados de periódicos e congressos nacionais e internacionais. As técnicas identificadas foram analisadas considerando-se o número de vezes em que apareceram nos artigos analisados e os objetivos de desempenho propostos por Slack et al. (2009). Como resultado obteve-se um framework para padronização de processos adaptado às necessidades do periódico estudado e viável de ser utilizado de forma mais ampla, dada a sua similaridade estrutural com o modelo proposto por Campos (2004), uma referência brasileira na área.
Definition of a process standardization framework for a scientific journal based on a literature review and its performance objectives
Keywords: Process Standardization; Scientific Journal; Editorial Team; Process Management; Literature Review; Performance Objectives; Padronização de Processos; Periódico Científico; Equipe Editorial; Revisão da Literatura; Objetivos de Desempenho